Impairment of Executive Functions Associated With Lower D-Serine Serum Levels in Patients With Schizophrenia - Hons, Jaromir; Zirko, Rastislav; Vasatova, Martina; Doubek, Pavel; Klimova, Blanka; Masopust, Jiri; Valis, Martin; Kuca, Kamil (Frontiers in Psychiatry, 2021)
A core symptom that is frequently linked with dysregulation of glutamatergic neurotransmission in regard to schizophrenia is impairment or damage of executive functioning as a component of cognitive deficiency. The amino acid D-serine plays the role of an endogenous co-agonist at the glutamatergic N-methyl-D-aspartate (NMDA) receptor glycine modulatory site. Considerably reduced serum levels of D-serine were found in patients suffering from schizophrenia compared with healthy control participants. An increase in D-serine led to augmented cognitive functionality in patients suffering from schizophrenia who were undergoing clinical trials and given the treatment of first- and second-generation antipsychotics. The study proposed the hypothesis that the D-serine blood serum levels may be linked with the extent of executive functionality in those suffering from the mental illness in question. For the purpose of examining executive function in such patients, the Rey-Osterrieth Complex Figure, Trail Making, and Wisconsin Card Sorting tests were applied (N=50). High-performance liquid chromatography was used to gauge the total serine and D-serine levels. The extent of damage was examined through neuropsychological tests and was found to be considerably negatively linked to the total serine/D-serine ratio (r=-0.29, p<0.05) in the sample being considered. A lower average serum level of D-serine was observed in participants with the worst performance compared with those displaying the best performance – this was true when the patients were split into quartile groups based on their results (p<0.05). The findings of modified D-serine serum levels and the D-serine/total serine ratio linked to the extent of damage in executive functioning indicate that serine metabolism that is co-responsible for NMDA receptor dysfunction has been changed.